2016
DOI: 10.1093/cid/ciw803
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact and Cost-Effectiveness of Xpert MTB/RIF Testing in Hospitalized Patients with Presumptive Pulmonary Tuberculosis in the United States

Abstract: SummaryIn hospitalized patients with presumptive pulmonary tuberculosis in a low-burden setting such as the United States, GeneXpert MTB/RIF molecular testing can reduce the duration of airborne infection isolation and is comparably sensitive, more specific, and more cost-effective than smear microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
45
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 34 publications
7
45
1
Order By: Relevance
“…Our study result demonstrated that GeneXpert testing among patients with suspected TB is very cost-effective. This cost estimate is in line with a study in China [32] and the United States [33] that found incorporating GeneXpert in the TB diagnostic algorithms was highly cost-effective.…”
Section: Discussionsupporting
confidence: 87%
“…Our study result demonstrated that GeneXpert testing among patients with suspected TB is very cost-effective. This cost estimate is in line with a study in China [32] and the United States [33] that found incorporating GeneXpert in the TB diagnostic algorithms was highly cost-effective.…”
Section: Discussionsupporting
confidence: 87%
“…Data on cost and cost-effectiveness of Xpert in diverse settings had been reported. Xpert was more sensitive, comparably specific, and more cost-effective than smear microscopy in intermediate and low burden areas (16,17). Xpert was superior over microscopic determination of drug susceptibility (MODS) in high TB/HIV prevalence setting (18).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, Ultra would be more cost-effective comparing with 2 Xpert tests for smear-negative PTB diagnosis. Cowan et al (21) reported that the two Xpert tests strategy was more expensive but still cost-effective compared with 3 smears. Due to the unavailable of Ultra in most of countries nowadays, our results suggested that two Xpert tests can benefit the poor diagnosis of smear-negative TB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both methods, however, have low clinical sensitivity for paucibacillary TB cases, which account for >60% of new TB cases each year in emerging TB-endemic areas such as China (1, 4, 5). The PCR-based Xpert MTB/RIF assay can increase the diagnosis speed and clinical sensitivity in multibacillary TB, but it still requires sputum or invasive biopsy specimens, exhibits moderate clinical sensitivity in patients with paucibacillary TB (e.g., Mycobacterium tuberculosis ( Mtb ) culture- or smear-negative TB cases), and cannot differentiate between live and nonviable Mtb bacilli to monitor response to anti-TB therapy (6–10). Blood-based IFN- Îł release assays measure ex vivo immune responses to assay-introduced Mtb antigens and cannot distinguish between active TB and latent TB infection (11, 12).…”
mentioning
confidence: 99%